Photocatalytic Activity Of Nanostructured Tubular TiO₂ Synthesized Using Kenaf Fibers As A Sacrificial Template - Moriga, Toshihiro; Osman, EdyNoor; Abd Manaf, Mohd Edeerozey; Abd Rashid, Mohd Warikh; Murai, Kei-ichiro; Horikawa, Toshihide (Elsevier, 2018)
The photocatalytic oxidation of various organic pollutants under UV irradiation can be enhanced by using ti-tanium dioxide (TiO2) photocatalyst. In this study, tubular TiO2 nanostructures were synthesized in a single step by depositing titanium (IV) isopropoxide precursor on kenaf fibers used as a sacrificial template. In the calci-nation temperature range of 500–700 °C, the produced tubular TiO2 predominantly contained the anatase phase. X-ray diffraction studies were performed to examine the crystallinity and crystallite size of the produced tubular TiO2, while its photocatalytic activity was determined by monitoring the degradation of methylene blue under ultraviolet irradiation. The obtained results showed that tubular TiO2 formed at 500°C exhibited the smallest crystallite size of 9.27 nm and fastest photocatalytic oxidation rate.